The Adolescent Resilience Questionnaire: Validation of a Shortened Version in U.S. Youths - Anderson, Jacqueline R.; Killian, Michael; Hughes, Jennifer L.; Rush, A. John; Trivedi, Madhukar H. (Frontiers in Psychology, 2020)
Introduction Resilience is a factor in how youth respond to adversity. The 88-item Adolescent Resilience Questionnaire is a comprehensive, multi-dimensional self-report measure of resilience developed with Australian youth. Methods Using a cross-sectional adolescent population (n = 3,222), confirmatory factor analysis was conducted to replicate the original factor structure. Over half of the adolescents were non-white and 9th graders with a mean age of 15.5. Results Our exploratory factor analysis shortened the measure for which we conducted the psychometric analyses. The original factor structure was not replicated. The exploratory factor analysis provided a 49-item measure. Internal consistency reliability for all 12 factors ranged from acceptable (α> 0.70–0.80). The revised factor total scores were highly and significantly correlated with item–total correlation coefficients (r > 0.63, p < 0.001). Conclusion This revised shorter 49-item version of the Adolescent Resilience Questionnaire could be deployed and has acceptable psychometric properties.